Building School - Family Synergy in Urban Early Childhood Education: A Case Study on Parental Participation at PAUD Al- Hikmah, Jakarta - Alawiyah, Nur Asiyah Tul; Erika, Masni (Kiddie: Early Childhood Education and Care Journal, 2025)
This study aims to describe parental participation in parenting activities at PAUD Al-Hikmah, Jakarta, and identify the obstacles faced in building school–family synergy. Using a qualitative case study design, data were collected through interviews, observations, and documentation. The findings show that parental participation is still limited due to parents’ work commitments, children being cared for by other guardians, inflexible activity schedules, and uneven levels of involvement. These constraints hinder effective collaboration between school and family. The study recommends adaptive communication strategies, such as flexible scheduling, the use of online platforms, and personal approaches to parents, so that parenting activities can become sustainable collaborative spaces supporting early childhood education.